Impact of COVID-19 on migrant populations in high-income countries: a systematic review. (20th October 2021) - Hayward, SE; Deal, A; Cheng, C; Orcutt, M; Norredam, M; Veizis, A; Campos-Matos, I; McKee, M; Kumar, B; Hargreaves, S
Abstract: Background: Migrants in high-income countries (HICs) may have been disproportionately affected by the COVID-19 pandemic, yet the extent to which they are impacted, and their predisposing risk factors, are not clearly understood. We did a systematic review to assess clinical outcomes, indirect health and social impacts, and key risk factors in migrants. Methods: Our systematic review following PRISMA guidelines (PROSPERO CRD42020222135) identified peer-reviewed and grey literature relating to migrants (foreign-born) and COVID-19 in 82 HICs. Primary outcomes were cases, hospitalisations and deaths from COVID-19 involving migrants; secondary outcomes were indirect health and social impacts and risk factors. Results: 3016 data sources were screened with 158 from 15 countries included in the analysis. We found migrants are at increased risk of SARS-CoV-2 infection and are over-represented among cases (e.g. constituting 42% of cases in Norway [to 27/4/2020], 26% in Denmark [to 7/9/2020], and 32% in Sweden [to 7/5/2020]); some datasets from Europe show migrants may be over-represented in deaths with increased all-cause mortality in migrants in some countries in 2020. Undocumented migrants, migrant health and care workers, and migrants housed in camps have been especially affected, with certain nationality groups disproportionately impacted. Migrants experience a range of risk factors for COVID-19, including high-risk occupations, overcrowded accommodation, and barriers to healthcare including inadequate information, language barriers, and reduced entitlement. Conclusions: Migrants in HICs are at high risk of COVID-19, with a range of specific risk factors that have not been well-considered in the public health response to date. These data are of immediate relevance to the policy response to the pandemic, with strategies urgently needed to reduce transmission. Migrant populations must also be better considered in national plans for COVID-19 vaccination roll-out. On behalf of ESGITM Key messages: Migrants in high-income countries may be disproportionately represented in COVID-19 infections and deaths, with higher levels of many vulnerabilities and risk factors. Migrants must be better included in all aspects of the pandemic response, including vaccination roll-out.